Mobilisation of Income Zakat Payment In Indonesia - Doktoralina, Caturida Meiwanto; Bahari, Zakaria; Abdullah, Sakinatul Raadiyah (IKONOMIKA, 2018)
The objectives of the study establish a conceptual framework to strengthen institutions that support the mobilisation of paying zakat and to identify the concept of the cultural factor of mutual assistance in paying zakat. This is Important because the institution of zakat has implemented the collection of zakat. Meanwhile, the culture of mutual assistance in Indonesia can be a power of zakat payment mobilisation to gain the blessings of Allah SWT. This paper presents the factors of determining mobilisation of zakat payments, e.g., are awareness, willingness to donate, confidence in collection and distribution with the latest development of technology. The implication of this study will help mobilise the payment of income zakat in Zakat Institutions. This study uses the documentation analysis method. Factors affecting mobilisation are awareness, willingness to donate, confidence in collection and distribution with the latest development of technology to help mobilise the payment of income zakat in Zakat Institutions. Keywords : Collection, Mobilisation, Payment, Sincerity, Zakat